An exploratory single-cell analysis of peripheral blood mononuclear cells from vedolizumab-treated Crohn’s disease patients identifies response-associated differences among the plasmacytoid dendritic cells and classical monocytes - Li Yim, Andrew Yung Fong; Hageman, Ishtu; Joustra, Vincent W.; Elfiky, Ahmed M. I. M.; Ghiboub, Mohammed; Levin, Evgeni; Verhoeff, Jan; Verseijden, Caroline; Admiraal, Iris; de Krijger, Manon; Wildenberg, Manon E.; Mannens, Marcel; et al. (Frontiers in Immunology, 2025)
BackgroundVedolizumab (VDZ) is a monoclonal antibody approved for the treatment of Crohn’s disease (CD). Despite its efficacy, non-response to VDZ is common in clinical practice with no clear understanding of how it manifests. Here, we performed an exploratory study characterizing the cellular repertoire of responders and non-responders to VDZ during treatment.MethodsPeripheral blood mononuclear cells (PBMCs) were isolated from CD patients on VDZ treatment that were either steroid-free responder (N = 4) or non-responder (N = 4). Response was defined as ≥3 drop in Simple Endoscopic Score for Crohn’s Disease (SES-CD) in combination with a ≥50% reduction in C-reactive protein (CRP) and fecal calprotectin and/or a ≥3 point drop in Harvey-Bradshaw Index (HBI). Single-cell repertoires were characterized using single-cell RNA-sequencing (scRNAseq) and mass cytometry by time of flight (CyTOF).ResultsNon-responders to VDZ presented more T cells, but fewer myeloid cells, with plasmacytoid dendritic cells (pDCs) being the most notably lower among non-responders. At a transcriptional level we observed that T-cell expression of genes involved in for Toll-like receptor (TLR), NOD-like receptor (NLR), and mitogen-activated protein kinases (MAPK) signaling pathways were decreased among non-responders. Similarly, non-responder-derived classical monocytes presented lower expression of genes involved in cytokine-cytokine receptor signaling.ConclusionsNon-response to VDZ during treatment is associated with differences in abundance and expression among T and myeloid cells.